A Missed Opportunity and Limited Vision for Internationalization - de Wit, Hans; Jones, Elspeth (International Higher Education, 2022)
The Common Statement in Support of International Education and Mobility, recently issued by the international education organizations of nice Western countries as a result of their 2021 summit is a missed opportunity. It does not include the perspectives of other regions of the world, and promotes physical mobility, in contrast to the impetus given to more inclusive virtual mobility initiatives during the COVID-19 pandemic.